Teachers' perceptions toward EFL textbook - Indah Okitasari; Dian Palupi (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2019)
Teachers have an important role in determining a good textbook for students. However, it seems difficult because the teachers should have academic and non-academic considerations. This qualitative research aims to investigate 10 teachers’ perceptions toward the use of EFL textbook and the strength and weakness of the ’English Ok’ textbook used in 5 schools in Bandung. Through the questionnaire, interview and document analysis, 80% of teachers said that the use of the textbook was helpful and important for them. They used the textbook as the source of learning and made an effective time in transferring the knowledge. Meanwhile, 20% of teachers perceived that they preferred to use adapting materials from other resources as the materials than the book. In terms of practical consideration (accessibility, attractiveness, accessibility, and publication), layout and design, content (materials, practice, and activities), learners’ need and language accuracy, the ‘English ok’ book was considered as a good textbook. The weaknesses of the textbook were the unavailability of the audiocassette, answer sheet and exercise preparation for the national examination. Involving more participants are recommended to find out the perceptions of anti-textbook teachers.